A deeper dive: A mixed methods approach to risk tolerance. Issue 2 (29th June 2021) - Lurtz, Meghaan R.; Archuleta, Kristy; Kothakota, Michael; Jorgensen, Timi Joy
Abstract: Most risk tolerance studies are quantitative, even though many factors that may affect the manifestation of risk tolerance are qualitative. This study employed a mixed‐methods approach to investigate how individuals consider risk tolerance as it relates to their financial situation. Fuzzy‐trace theory, a psycholinguistic theory of risk processing rooted in prospect theory that is becoming increasingly popular in the medical field, guided the study. Quantitative results indicate that stated versus revealed measures of risk tolerance are not consistent for most people. However, higher risk literacy increases the likelihood of consistency. Qualitative results reveal that individuals perceive risk tolerance through various lenses, including knowledge, values, emotions, and personal experience.